The utilization of rock phosphate (natural defluorinated calcium phosphate or NDCP) in laying hens diet to replace dicalcium phosphate - Sinurat, A.P; Dharsana, R; Pasaribu, T; Panggabean, T; Habiebie, A (Indonesian Journal of Animal and Veterinary Sciences, 1996)
An experimentwas conducted to study the utilization of local rock phosphate or natural defluorinated calcium phosphate (NDCP) as phosphorus source for layer chickens by using the imported dicalcium phosphate (DCP) as a reference. Eight experimental diets consisted of 2 source of phosphorus (DCP and NDCP) and 4 dietary total P levels (0.4, 0.5, 0.6 and 0.7%) were formulated. Each diet was fed to 24 pullets (6 replicates with 4 birds each) from 20 weeks of age to 14 weeks of egg production. Observations were made on feed consumption, egg production, egg weight, mortality, egg quality, Ca and P retention and ash content of tibial bones . Results showed no significant effect of different source and level of Â phosphorus tested on egg production (% HD), feed consumption, egg weight and mortality rates . Egg shell thickness was depressed in NDCP diet as compared with DCP, however this only occurred at firstmonth of production. It is concluded that the NDCP can be used in layers diet to replace DCP as phosphorus source. The relative biological value of phosphorus inNDCP is 96% for layers. Â  Keywords: Rock phosphate, NDCP, layers, phosphorous